Cytoreductive surgery and hyperthermic intraperitoneal chemotherapy for peritoneal malignant tumors in children: Initial experience in a single institution - Zhu, Zhiyun; Chang, Xiaofeng; Wang, Jiarong; Yang, Shen; Qin, Hong; Yang, Wei; Cheng, Haiyan; Meng, Deguang; Wang, Huanmin (Frontiers in Surgery, 2023)
Background Peritoneal malignant tumors in children are rare, but commonly associated with disease progression and poor outcome. The successful treatment experience of Cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) in adult peritoneal carcinoma has been applied to pediatric peritoneal malignancy in recent years [1-3]. However, the patients with desmoplastic small round cell tumor (DSRCT) accounted for the majority treated with HIPEC in the previous studies. The role of HIPEC remains controversial due to the rarity of the disease and the limited sample size of studies [3-5]. Additionally, in the cases using HIPEC except DSRCT were mainly small case reports with unclear outcome [2,6-9]. We presented our experience in the treatment of pediatric peritoneal malignancies using CRS and HIPEC, with more emphasizing on the safety, feasibility and the short-time outcome. Methods A retrospective query from December 2019 to February 2022 identified 19 children treated with peritoneal malignanies underwent CRS and HIPEC in our institution. Clinical characteristics, therapies and outcomes were summarized and analyzed. Results The median age of the patients was 6.4 years (range, 0.7~13.9 years). The histologic types included rhabdomyosarcoma (7), nephroblastoma (2), clear cell sarcoma of the kidney (2), undifferentiated sarcoma (2), immature teratoma (1), peritoneal serous carcinoma (1), malignant rhabdoid of kidney (1), malignant germ cell tumor (1), neuroblastoma (1) and epithelioid inflammatory myofibroblast sarcoma (1). 7 cases underwent initial operation and 12 cases received reoperation for tumor recurrence. The median PCI (peritoneal carcinomatosis index) was 5 (range, 2~12). There was no perioperative death or life-threatening complications of HIPEC. Two patient had grade 3 complications of wound infection and wound dehiscence. With a median follow-up time of 14 months (range, 1.5-31 months), 14 patients were alive and 5 died of tumor recurrence. In the 14 patients who are alive, 2 relapsed after CRS+HIPEC and then received radiotherapy and molecular targeted therapy or chemotherapy. Conclusions HIPEC is safe and feasible in children, without increasing serious complications in peri- and post-operative period. The complication is acceptable. The short-term outcome shows possible effectiveness in pediatric peritoneal malignant tumors. The long-term effectiveness need be verified by additional cases and long-time follow-ups.